2018
DOI: 10.1111/birt.12373
|View full text |Cite
|
Sign up to set email alerts
|

Bearing witness: United States and Canadian maternity support workers’ observations of disrespectful care in childbirth

Abstract: Doulas and nurses frequently said that they witnessed verbal abuse in the form of threats to the baby's life unless the woman agreed to a procedure, and failure to provide informed consent. Reports of witnessing some types of disrespectful care in childbirth were relatively uncommon among respondents, but witnessing disrespectful care was associated with an increased likelihood to leave maternity support work within three years, raising implications for the sustainability of doula practice, nursing work force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 43 publications
2
38
0
3
Order By: Relevance
“…Studies cross-referencing these issues were published only within the past 2-3 years, [14][15][16]25 which indicates that until recently, there has been little exchange of information by researchers on the relationship between disrespectful maternity care, PTSD, and postpartum PTSD. 28 yielded very few cross-references between these phenomena.…”
Section: Resulting From Disrespectful Carementioning
confidence: 99%
See 2 more Smart Citations
“…Studies cross-referencing these issues were published only within the past 2-3 years, [14][15][16]25 which indicates that until recently, there has been little exchange of information by researchers on the relationship between disrespectful maternity care, PTSD, and postpartum PTSD. 28 yielded very few cross-references between these phenomena.…”
Section: Resulting From Disrespectful Carementioning
confidence: 99%
“…[14][15][16] Other types of disrespectful maternity care may include the absence of translation services; withholding or distorting information; coercion and unfounded threats of harm to baby to gain consent for unwanted procedures; and lack of informed consent. In some countries, disrespectful maternity care consists of physical or sexual abuse in the form of hitting; unnecessary restraints; exposure of the woman's sexual parts; rough vaginal examinations; and other abusive treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process also requires that the woman has crucial information to make her decision, including her provider's success rate with the intervention; she should not feel pressured or coerced by her provider. Disturbingly, in a recently published study, Morton et al reported that nearly two‐thirds of doulas and labor and delivery nurses working in the United States and Canada who completed a survey (N = 2781) witnessed providers occasionally or often engage in procedures without giving women the time or option to consider them. Even more disturbing, one‐fifth of respondents reported that they saw providers occasionally or often perform procedures on women who explicitly declined them.…”
Section: Woman‐centered Care In the Age Of Childbirth Medicalizationmentioning
confidence: 99%
“…Some issues in our system are rooted in discrimination and ignorance. For example, in Morton et al's analysis of survey responses from US nurses and doulas, they found that white, non‐Hispanic women had less than half the risk of non‐white, non‐Hispanic women of undergoing extra procedures during labor because of their race or ethnicity (adjusted odds ratio [aOR], 0.42; 95% CI, 0.29‐0.61).…”
Section: Woman‐centered Care In the Age Of Childbirth Medicalizationmentioning
confidence: 99%